2017
DOI: 10.4314/jab.v106i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Étude ethnobotanique et phytochimique de <i>Momordica charantia Linn (Cucurbitaceae) à Cotonou</i> au Bénin

Abstract: RÉSUMÉObjectif : La présente étude, sur Momordica charantia Linn (Cucurbitaceae), communément appelé margose une plante très utilisée pour le traitement de nombreuses maladies, est menée dans la ville de Cotonou au Bénin. Elle vise à vérifier la portée scientifique des usages empiriques que fait la population de cette plante, afin de promouvoir son utilisation sans risque. Méthodologie et résultats : Une étude ethnobotanique est réalisée auprès de 32 vendeurs des trois marchés de plantes médicinales les plus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
1
2
2
Order By: Relevance
“…Alkaloids and cyanogenic derivatives were undetectable in all juices. These results are in contradiction with those observed by Johnson et al [ 39 ] who have revealed the presence of alkaloids and free anthracene but not triterpenoids, coumarins, and saponins in M. charantia also collected from Benin. According to other studies, M. charantia should contain flavonoids, tannins, saponins, and even alkaloids [ 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Alkaloids and cyanogenic derivatives were undetectable in all juices. These results are in contradiction with those observed by Johnson et al [ 39 ] who have revealed the presence of alkaloids and free anthracene but not triterpenoids, coumarins, and saponins in M. charantia also collected from Benin. According to other studies, M. charantia should contain flavonoids, tannins, saponins, and even alkaloids [ 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…These results were similar to our previous recent findings [ 1 ]. However, they were in contradiction with those obtained by Johnson et al [ 46 ] who have revealed the presence of alkaloids and free anthracene but not triterpenoids, coumarins, and saponins in M. charantia also collected from Benin. This discrepancy could be related to several parameters: parts of plant used, nature of solvent, and mode of preparation, geographical origin, and genetic divergences of the strains used [ 47 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Selon l'interview, c'est une plante à la fois alimentaire et thérapeutique utilisée plus par les hommes que les femmes. Cette différence pourrait être expliquée par le fait que les hommes utilisent la plante lors des luttes traditionnelles pour affaiblir un adversaire ou lors des rites traditionnels au Bénin (Johnson, 2017).…”
Section: Consommation Et Usages De M Charantiaunclassified
“…Dans ce contexte la connaissance ethnobotanique des ressources végétales est d'une grande importance pour une bonne préservation de ces ressources naturelles (Akabassi et al, 2017 ;Yedomonhan et al, 2017). Il en est de même pour Momordica charantia, à cause des propriétés thérapeutiques des feuilles et des tiges ignalées au Bénin par Johnson et al, (2017). Cependant, l'exploitation et l'usage du fruit et des graines par lespopulations locales restent inconnus.…”
Section: Introductionunclassified